2003
DOI: 10.1159/000071215
|View full text |Cite
|
Sign up to set email alerts
|

Sleep among Habitually Violent Offenders with Antisocial Personality Disorder

Abstract: The aim of the present study was to characterize the subjective and objective sleep and sleep quality in habitually violent offenders with DSM-IV diagnosis of antisocial personality disorder using a sleep questionnaire, actigraphy, polysomnography and power spectral analysis. Subjects for the study were 19 drug-free males (mean age ± SEM 30.7 ± 2.58 years) recruited from a forensic psychiatric examination in a special ward of a university psychiatric hospital. The most striking finding was the high amount of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…Additionally, those who reported more externalizing symptoms were more likely to experience poorer sleep quality than those scoring lower on these measures. This is in accordance with previous studies, which have shown that incarcerated individuals and those with personality disorders who commit aggressive acts have poorer sleep quality than individuals scoring lower on measures of ASB (Lindberg et al 2003 ;Ireland & Culpin, 2006 ;Semiz et al 2008). The present study extends this finding to members of the general population.…”
Section: Limitationssupporting
confidence: 93%
“…Additionally, those who reported more externalizing symptoms were more likely to experience poorer sleep quality than those scoring lower on these measures. This is in accordance with previous studies, which have shown that incarcerated individuals and those with personality disorders who commit aggressive acts have poorer sleep quality than individuals scoring lower on measures of ASB (Lindberg et al 2003 ;Ireland & Culpin, 2006 ;Semiz et al 2008). The present study extends this finding to members of the general population.…”
Section: Limitationssupporting
confidence: 93%
“…It is problematic to extrapolate the findings in waking EEG to sleep EEG, but spectral profiles both in the ‰, , · and ß frequency bands of subjects' waking EEGs have been found to be highly correlated with their sleep EEGs [48]. In our previous PSG studies [17,18], both posterior (derivation O2-P4) ‰ and powers were significantly increased in the antisocial offenders compared with the healthy controls. The decline in SWS as well as in ‰ power, which in sleep architecture normally occurs in the course of aging, may be delayed in ASP -the idea associated previously with childhood ADHD.…”
Section: Discussionmentioning
confidence: 94%
“…In a study by Ramos Platon et al [14], 13 non-medicated prepubertal children with ADHD displayed a higher slow wave sleep (SWS) percentage compared with normal age-matched controls. In our previous studies [17,18], habitually violent, homicidal offenders meeting the DSM-IV criteria for ASP and Cloninger type 2 alcoholism had increased amounts of SWS, particularly stage 4 (S4) sleep, as compared with age-and gender-matched healthy controls. Interestingly, ASP and childhood ADHD appear to be the only psychiatric disorders reported to associate with an increase in deep sleep.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations